Dynamics Analysis and Simulation of the Thread Take-up and Needle Bar Mechanism in High Speed Industrial Flat Sewing Machine - Wang Binquan; Zhang Chun; Du Xiaotian; Su Wei (Jixie chuandong)
Aiming at the high speed requirement of industrial flat sewing machine,The kinematics and dynamics models of the thread take-up and needle bar mechanisms are established by using the closed-loop vector method and the simultaneous constraint method,and its kinematics and dynamics equations are deduced.Applying the Simulink module built in the Matlab,the simulink model of the mechanism is built and executed.By analyzing the inertia force and the force in kinematic pair on the mechanism,the conclusion that there is a periodic force which liked an impact force acting on each kinematic pair is obtained.And the periodic forces would cause the rack vibration as well as the abrasion of the kinematic pairs.The analysis for the thread take-up and needle bar mechanism based on the dynamic static analysis method lays a foundation for the further improvement of sewing machine.